Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1089/104303403322542248
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Interactions Involved in Adenoviral-Mediated Gene Delivery After Systemic Administration in Non-Human Primates

Abstract: Adenovirus serotype 5 (Ad5)-based vectors can bind at least three separate cell surface receptors for efficient cell entry: the coxsackie-adenovirus receptor (CAR), alpha nu integrins, and heparan sulfate glycosaminoglycans (HSG). To address the role of each receptor involved in adenoviral cell entry, we mutated critical amino acids in fiber or penton to inhibit receptor interaction. A series of five adenoviral vectors was prepared and the biodistribution of each was previously characterized in mice. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 32 publications
5
87
1
Order By: Relevance
“…This is in agreement with studies in mice that demonstrated CARindependent uptake of adenovirus by hepatocytes mediated by heparan sulfate glycosaminoglycans. 30 We have described this finding before in the context of the limited hepatotoxicity of systemically administered ONYX-015, which might be influenced by changing accessibility of CAR with repeated virus administrations. 9 In agreement with CAR's function as a tight-junction protein, we found particularly strong expression of the protein around liver canaliculi, bile ducts and pancreatic ducts.…”
Section: Discussionmentioning
confidence: 89%
“…This is in agreement with studies in mice that demonstrated CARindependent uptake of adenovirus by hepatocytes mediated by heparan sulfate glycosaminoglycans. 30 We have described this finding before in the context of the limited hepatotoxicity of systemically administered ONYX-015, which might be influenced by changing accessibility of CAR with repeated virus administrations. 9 In agreement with CAR's function as a tight-junction protein, we found particularly strong expression of the protein around liver canaliculi, bile ducts and pancreatic ducts.…”
Section: Discussionmentioning
confidence: 89%
“…3,17-23 Ablation of CAR-and integrin-binding motifs in the Ad5 capsid did not alter Ad5 biodistribution in cynomolgus monkeys, indicating that an alternate transduction pathway may be responsible for liver transduction in these animals. 19 Alternative serotypes (Ad35) have also shown decreased liver transduction following i.v. delivery in non-human primates, although viral genomes can be detected in hepatic samples.…”
mentioning
confidence: 99%
“…24 Other studies have obtained similar results using fiber-pseudotyped Ad5 vectors (Ad5/35 and Ad5/11) where significant gene transduction by these vectors was only observed in the marginal zone of splenic follicles. 18 Importantly, none of the reported modifications incorporated in the Ad5 capsid, via ablation of fiber and/or penton binding to natural receptors, 19 have shown significantly reduced hepatic transduction or viral genome accumulation in non-human primates. In the present study, we document the transduction profiles and viral genome accumulation of Ad5 and FX-binding-ablated Ad5 vectors in Microcebus murinus to identify whether the Ad5-FX pathway modulates Ad5 biodistribution in non-rodent species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to inhibit hepatocyte and/or liver Kupffer cell uptake by ablating CAR-or integrin-binding motifs in the Ad capsid have been largely unsuccessful, however, indicating that native Ad tropism determinants contribute little to vector hepatotropism in vivo. [40][41][42][43][44] These data notwithstanding, work by several groups has implicated the fiber protein as a major structural determinant of liver tropism in vivo (reviewed by Nicklin et al 45 ). For example, shortening of the native fiber shaft domain of the Ad5 fiber 46 or replacement of the Ad5 shaft with the short Ad3 shaft domain 47 was shown to attenuate liver uptake in vivo following intravenous delivery.…”
Section: Transductional Targeting Of Admentioning
confidence: 99%